Assessing Urban Green Space Accessibility for Sustainable Development in Mostaganem, Algeria: A Space Syntax Approach - Benameur, Okba; Leghrib, Fouad; Laroui, Abdelbasset (Alanya Üniversitesi, 2024)
The rapid urbanization of Mostaganem, Algeria, has led to significant challenges in the accessibility of urban green spaces (UGS), crucial for promoting environmental sustainability and public health. This study uses a space syntax approach, specifically angular segment analysis (ASA), to assess UGS accessibility at city-wide and local scales. By integrating quantitative measures like